(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Conducted during the National Peking Opera Company’s tour of Brazil in November 2024, this interview interprets the opportunity to listen to its artists as a form of living archive, contributing to the construction of the memory of Chinese theater on Brazilian stages. In their reflections, Guan Xiaohui, Liu Kuikui, Jiang Meiyi, and Wu Zeyu discuss the troupe’s legacy, the repertoire selected for the performances, the role of Peking Opera in the cultural diplomacy of the People’s Republic of China in the 1950s and today, as well as the genre’s continuity at the intersection of tradition and contemporary innovation.